HIROSHIMA, THE VIETNAM VETERAN'S MEMORIAL, AND THE GULF WAR: POST-NATIONAL SPECTACLES - Pease, Donald (Surfaces, 1994)
In the context of changing structures of global power, this essay offers a theoretical and historical analysis of prevailing U.S. representations of itself and its Others. Taking as its point of departure the Gulf War, it examines the national narratives of impending nuclear desaster, the Vietnam syndrome, and the erection of the Vietnam Veterans Memorial. It concludes by interpreting the Rodney King incident as the activation of an alternative memory that cannot be subsumed by the image of a New World Order.